Initial human and financial capital as predictors of new venture performance - Cooper, Arnold C.; Gimeno-Gascon, F.Javier; Woo, Carolyn Y. (Journal of Business Venturing, 1994)
This research seeks to predict the performance of new ventures based on factors that can be observed at the time of start-up. Indicators of initial human and financial capital are considered to determine how they bear upon the probability of three possible performance outcomes: (1) failure, (2) marginal survival, or (3) high growth. Four categories of initial human and financial capital are examined. General human capital, represented here by the entrepreneur's education, gender, and race, may reflect the extent to which the entrepreneur has had the opportunity to develop relevant skills and contacts. Management know-how, embodied in the entrepreneur or available through advisors or partners, reflects management-specific skills and knowledge, without regard to the kind of business. Industry-specific know-how reflects specific experience in similar businesses. Financial capital is one of the most visible resources; it can create a buffer against random shocks and allow the pursuit of more capital-intensive strategies, which are better protected from imitation. The study utilizes a longitudinal study of 1053 new ventures, representative of all industry sectors and geographical regions. The research departs from most previous studies in considering different measures of performance (marginal survival and growth) and in considering explicitly whether the factors contributing to marginal survival differ from those contributing to high growth. It was found that measures of general human capital influenced both survival and growth (except for gender, with women-owned ventures being less likely to grow, but just as likely to survive). Management know-how variables had more limited impact. Having parents who had owned a business contributed to marginal survival, but not to growth. Number of partners contributed to growth but not to survival. Management level, prior employment in non-profit organizations or not having been in the labor force, and the use of professional advisors did not have significant effects. Industry-specific know-how contributed to both survival and growth. Amount of initial financial capital also contributed to both. The usefulness of the model is enhanced by the fact that the resource variables considered are relatively easy to assess and all can be considered at the time of start-up. Although some of the human capital variables cannot easily be changed, the benefits or risks associated with each can be assessed. In some cases, potential problems can be identified so that plans can be modified to improve prospects. Overall it appears that, using a model based upon the initial human and financial capital of the venture, it is possible to predict the performance of new ventures with some degree of confidence.